(Sub)national Principals, Legislative Agents: Patronage and Political Careers in Mexico. (July 2015) - Kerevel, Yann P.
To what extent do external actors control the careers of national legislators in federal systems? Although previous research has demonstrated that multiple principals shape legislative behavior in federal systems, prior studies have been much less successful at demonstrating the relative power of each of these actors over the careers of federal legislators. Using an original data set on the career paths of Mexican federal legislators, this study seeks to determine the relative importance of governors, presidents, and other party elites in shaping the future career choices of national legislators in federal systems. I find that legislators who share partisanship with the president or their governor are more likely to obtain patronage positions, while party leaders predominantly control access to the ballot. The findings also suggest that while governors and presidents can influence a subset of legislators, the large majority of legislators pursue future positions over which party leaders control access.